Flying after left ventricular assist device implantation. Issue 3 (20th October 2020) - Hanke, Jasmin S.; Schmack, Bastian; Merzah, Ali Saad; Bounader, Karl; Chatterjee, Anamika; Mariani, Silvia; Li, Tong; Klautzsch, Erik; Mueller, Florian; Homann, Katharina; Schoede, Alexandra; Haverich, Axel; et al.
Abstract: Literature on the air travel activities of patients supported by permanent mechanical assist devices is rare. To the best of our knowledge, no air travel guidelines or fitness prerequisites exist on whether and when ventricular assist device (VAD) patients are allowed to travel by plane after device implantation. In this study, we evaluated the topic of air travel after VAD implantation. This working group aimed to produce a report on air travel passengers supported by VADs, regarding their fitness to fly. Fifty left ventricular assist device (LVAD) patients were surveyed in a worldwide multicenter study. The single survey was performed with a multimethod design, including interviews conducted face‐to‐face, online, and on phone. Out of 50 patients, 97% described their traveling by aircraft as perfect and uneventful during the flight. Eighty‐five percent of the study participants consulted their medical practitioner before the flight. No patient reported the occurrence of a severe condition associated with flying. LVAD alarms, especially low flow alarms, did not occur in any of the devices. Thirty‐five percent of the surveyed patients, however, stated a major problem pertaining to the security check procedures at the airport. The results of this study suggest that commercial air travel is safe for stable patients on permanent VAD support and traveling can be resumed securely after VAD implantation. Conscientious preparation by packing necessary devices, fluids, medications, and careful preparation for the airport security check is recommended.